Assessment of Popular DFT and Semiempirical Molecular Orbital Techniques for Calculating Relative Transition State Energies and Kinetic Product Distributions in Enantioselective Organocatalytic Reactions - Schenker, Sebastian; Schneider, Christopher; Tsogoeva, Svetlana; Clark, Timothy (Journal of Chemical Theory and Computation, 2011)
The performance of computationally accessible levels of calculation for the transition states of organocatalytic reaction has been assessed. Reference post-Hartree-Fock single point energy calculations were used as standards for the gas-phase Born-Oppenheimer relative energies of pairs of alternative transition states that lead to the two product enantiomers. We show that semiempirical methods cannot even be relied on to yield qualitatively correct results. The geometries (optimized, for instance, with DFT) have a large impact on the results of high-level post-HF calculations, so that it is essential to use an adequate DFT technique and basis set. DFT can yield quantitatively correct results that are consistent with post-HF calculations if functionals that consider dispersion are used. Geometries for large systems show larger errors than those for smaller ones but are treated better by functionals such as M06-2X and w97Bxd that include dispersion implicitly or explicitly. Local correlation techniques introduce errors of comparable magnitude to those given by different levels of geometry optimization. We recommend RICC2/TZVP//M06-2X/TZVP, RI-MP2/TZVP//M06-2X/TZVP, and M06-2X/TZVP//M06-2X/TZVP calculations in that order, depending on the size of the system.

Silicon Lewis Acid Catalyzed [3+2] Cycloaddition Reactions of Hydrazones/Cyclopentadiene: Mild Access to Pyrazolidine Derivatives - Zamfir, Alexandru; Schenker, Sebastian; Bauer, Walter; Clark, Timothy; Tsogoeva, Svetlana (European Journal of Organic Chemistry, 2011)
A first and fairly mild metal-free catalytic route was developed for the [3+2] cycloadditions of different N-acylhydrazones to cyclopentadiene, providing the synthetically and biologically important five-membered cyclic compounds pyrazolidines. The reaction was successfully conducted in high yields (up to 99%) with high diastereoselectivities (up to 98: 2 dr) by using catalytic amounts of TMSOTf (trimethylsilyl triflate) as a readily available Lewis acidic catalyst. The experimental findings were supported by DFT calculations of the reaction mechanism. The theoretical and experimental diastereomeric excess values show good agreement, rendering the computations an efficient tool for predicting the selectivities in these and related reactions.
Keywords: Cycloaddition; Lewis acids; Nitrogen heterocycles; Hydrazones; Silicon; Density functional calculations

Synthesis and evaluation of new guanidine-thiourea organocatalyst for the nitro-Michael reaction: Theoretical studies on mechanism and enantioselectivity - Shubina, Tatyana; Freund, Matthias; Schenker, Sebastian; Clark, Timothy; Tsogoeva, Svetlana (Beilstein Journal of Organic Chemistry, 2012)
A new guanidine-thiourea organocatalyst has been developed and applied as bifunctional organocatalyst in the Michael addition reaction of diethyl malonate to trans-β-nitrostyrene. Extensive DFT calculations, including solvent effects and dispersion corrections, as well as ab initio calculations provide a plausible description of the reaction mechanism.